RACISM IN P. DJÈLÍ CLARK’S RING SHOUT (2020): A MARXIST PERSPECTIVE - Romansa, Erven Nofryan (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study analysed the racism in P. Djèlí Clark’s Ring Shout (2020) through a Marxist perspective by applying Cedric J. Robinson’s theory of racial capitalism and Antonio Gramsci’s concept of cultural hegemony. The researcher identifies the forms of racism depicted in the novel, examine the factors that contribute to the development of racism, and explore the impacts of racism on the characters and social structures portrayed. This research uses a qualitative descriptive method supported by Marxist literary approach, focusing on textual analysis of narrative events, dialogue, and character dynamics. The findings reveal that racism in Ring Shout appears in two primary forms: racial capitalism and cultural hegemony. Racial capitalism is represented through systemic exploitation, dehumanization, generational trauma, and institutional violence experienced by Black communities as a foundation for white economic and political power. Cultural hegemony is reflected through ideological manipulation, propaganda, religious discourse, and internalized racism. The study also concludes that the factors enabling racism to persist include structural racial hierarchy, material exploitation, systemic inequality, ideological domination, reproduction of consent, and cultural representation. Furthermore, the impacts of racism are shown through the development of resistance, expressed in the Black Radical Tradition and counter-hegemony movements.